TEKNOLOGI PENGOLAHAN PAKAN BERBAHAN INDIGOFERA ZOLLINGERIANA: PKM SEKOLAH PETANI DESA BUMDES BELABORI, MENGATASI KRISIS PAKAN DI MUSIM KEMARAU - Nadir, Marhamah; Prahesti, Kusumandari Indah; Laban, Sartika (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2020)
The availability of quality forage in the dry season is an obstacle to increase livesctok productivity.  The highest livestock production cost is feed, 60-70% of the total livestock business needs, so feed is the main component for animal husbandry development.   Indigofera zollingeriana is a legume plant that can grow well for a long time as a Forage (HMT), adapts very well to diverse environmental conditions, and is tolerant to long dry climates.  Another advantage of this plant is the high nutrient content, which is 35% protein, 15% crude fiber, 86% digestibility and very low anti-nutrient content.  The advantages of this plant need to be shared with the community, especially farmers.  Belabori Prosperous Village-owned business entity, is one of the BUMDES that has developed Indigofera since 2018, but the community has not utilized this plant optimally.  Belabori Village is an area with a significant number of cattle including cattle, goats and poultry.  To disseminate the use of Indigofera, Sekolah Petani Desa program is conducted, a learning house with lecturers, students, farmers, breeders and Bumdes to process Indigofera into nutritious feed and to be used in the dry season.  The purpose of ?Sekolah Petani Desa? activities is the transfer of technology of research results in the laboratory to the field.  SPD activities become a direct application media for campus research results to the field of farmers and ranchers and provide invaluable experience for researchers, ranchers and students who are directly involved in community service activities that are integrated with the field work practices of animal husbandry students.  This activity was successfully carried out and achieved the output target, namely breeders can process Indigofera into green concentrate flour, pellets, UMB, hay and silage.  Indigofera is the main source of protein for cattle and goats in the village of Belabori and is used by Bumdes to be a source of income through green concentrate businesses.